2019
DOI: 10.3390/insects10030077
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation Improves Stored Product Insect Pest Management

Abstract: There is a large suite of insects that attack anthropogenic agricultural goods after harvest. Proper sanitation programs for food facilities are now recognized as the foundation of good integrated pest management (IPM) programs for stored products throughout the post-harvest supply chain. While good sanitation programs are generally thought to reduce the abundance and diversity of insects, there has been less appreciation of the manifold ways that sanitation interacts with a range of other IPM tactics to modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 87 publications
(87 reference statements)
0
30
0
2
Order By: Relevance
“…In addition, we did see some indication of increased movement at the 72-h exposures compared to the 24-hr exposures, which was surprising, because in most studies knockdown after exposure usually leads to mortality rather than to recovery [20]. In earlier studies, Arthur [21,22] found that knockdown may lead to recovery in the presence of food sources that are reachable by insects, underlying the importance of sanitation in storage and processing facilities, which can adversely affect chemical control procedures [23]. In our experiments, the exposed adults remained on the commodity, which can be considered a food source.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, we did see some indication of increased movement at the 72-h exposures compared to the 24-hr exposures, which was surprising, because in most studies knockdown after exposure usually leads to mortality rather than to recovery [20]. In earlier studies, Arthur [21,22] found that knockdown may lead to recovery in the presence of food sources that are reachable by insects, underlying the importance of sanitation in storage and processing facilities, which can adversely affect chemical control procedures [23]. In our experiments, the exposed adults remained on the commodity, which can be considered a food source.…”
Section: Discussionmentioning
confidence: 67%
“…Additional experimental research is needed to clarify these effects. From the data available so far, it seems that this effect is realistic for pyrethroids [3], but not in IGRs, where effects on immature life stages are more irreversible [4,10,23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the researchers suggest that sanitation efforts need to be intensely focused on removing debris build up in the early stages of processing to reduce harborage sites for grain feeding insects. In addition to removing refugia, good sanitation improves residual and aerosolized insecticide efficacy [12,14,31].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the success of these methods, each has its own drawbacks, which may variously include insecticide toxicity, health hazards to workers [25], non-target effects on the environment [26,27] and the development of resistance in insects [28]. Therefore, there has been a push to develop biorational pest management methods in the postharvest supply chain [27,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%